Jenis â€“ Jenis Tanda Dalam Penokohan Cerpen â€œSyamsyÅ«n Al- JabbÄrâ€ Karya KÄmil KÄ«lani (Kajian Semiotika Charles Sander Pierce) - Masitoh, Anasmilah (Pascasarjana UIN Raden Mas Said Surakarta, 2021)
AbstrakThe types of signs in the Characterization of the Short Story of SyamsyÅ«n Al-JabbÄr by KÄmil KÄ«lanÄ« (Charles Sander Pierce's Semiotic Studies). This study discusses the types of signs contained in the short story SyamsyÅ«n Al-JabbÄr by KÄmil KÄ«lanÄ«. The purpose of this study is to describe the types of signs in the characterization of the short story SyamsyÅ«n Al-JabbÄr. The theory used in this study is the semiotics of Charles Sanders Pierce, known as the triangle theory of signs, namely: representamen, object, and interpretant. Pierce also divides the types of signs based on their objects into three, namely: icons, indexes, and symbols. The method used in this study is a qualitative descriptive method, namely examining the contents of the document. The results of this study are that there are three types of signs in SyamsyÅ«n Al-JabbÄr's short story that show characterizations, namely: icons, indexes, and symbols. The characterizations consist of SyamsyÅ«n Al-JabbÄr, Jamilah, Sultan, Dalilah, Blacksmith, and Minister. The signs are scattered on the 6 characters of the short story. There are 4 figures who have these three signs including Syamsun, Sultan, Dalilah, and Jamilah. As for the 2 figures who do not have these three marks, namely the blacksmith and the minister.Â Keyword : Short Story SyamsyÅ«n Al-JabbÄr, Â Charles Sander Pierce's Semiotic